Development of a Digital Library Infrastructure for the North: An Environmental Scanning Approach - Shiri, Ali; Rathi, Dinesh; Stobbs, Robyn; Campbell, Sandy; Farnel, Sharon; Cockney, Cathy; Maloney, Elaine (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2016)
This paper reports on an ongoing project: the development of an environmental scanning model as a basis for the creation of a digital library infrastructure for the Inuvialuit Settlement Region in Canada’s north. The model is proposed as a novel approach to community-focused digital library development and the paper also presents key emerging findings from the use of environmental scan model. Cette étude rend compte d’un projet en cours : le développement d’un modèle d’analyse de l’environnement comme base pour la création d’une infrastructure de bibliothèque numérique destinée à la région d’établissement Inuvialuit dans le Nord canadien. Le modèle est proposé comme une nouvelle approche pour le développement d’une bibliothèque numérique axé sur la communauté et l’étude présente également les principaux résultats issus de l’utilisation du modèle d’analyse de l’environnement.